What matters to users of services? An explorative study to promote shared decision making in health care. (6th March 2012) - Padgett, Kath; Rhodes, Christine; Lumb, Maureen; Morris, Penny; Sherwin, Sue; Symons, Jools; Tate, Joannie; Townend, Ken
Abstract Background Involving service users and carers in decisions about their health care is a key feature of health‐care practice. Professional health and social care students need to develop skills and attributes to best enable this to happen. Aims The aims were to explore service user and carer perceptions of behaviours, attributes and context required to enable shared decision making; to compare these perceptions to those of students and academic staff with a view to utilizing the findings to inform the development of student assessment tools. Methods A mixed methods approach was used including action learning groups (ALG) and an iterative process alongside a modified Delphi survey. Participants The ALGs were from an existing service user and carer network. The survey was sent to sixty students, sixty academics and 30 service users from 16 different professional disciplines, spanning four Universities in England. Results The collaborative enquiry process and survey identified general agreement that being open and honest, listening, showing respect, giving time and being up to date were important. The qualitative findings identified that individual interpretation was a key factor. An unexpected result was an insight into possible insecurities of students. Conclusions The findings indicate that distilling rich qualitative information into a format for student assessment tools could be problematic as the individual context could be lost, it is therefore proposed that the information could be better used as a learning rather than assessment tool. Several of those involved identified how they valued the process and found it beneficial.